2023
DOI: 10.4330/wjc.v15.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Does the intracoronary pressure differ according to two types (diffuse or focal) of coronary spasm?

Abstract: BACKGROUND Several reports show that two types of coronary vasospasm (diffuse and focal spasm) are associated with the severity or prognosis of coronary spasm in patients with vasospastic angina (VSA). It is unclear whether intracoronary pressure differs between the two spasm types. AIM To investigate such relationships using a pressure wire during the spasm provocation test (SPT) in patients with VSA. METHODS Eighty-seven patients with VSA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“… 33 However, the definition of focal spasm employed may lead to differences in interpretation. 28 In this study, the frequency of atherosclerotic lesions was increased by DM complications; however, focal spasm was rather unlikely to occur. Furthermore, our results suggest that focal spasm may have a poor prognosis when complicated with DM, even though it tends to be less common, and this finding might be noteworthy.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“… 33 However, the definition of focal spasm employed may lead to differences in interpretation. 28 In this study, the frequency of atherosclerotic lesions was increased by DM complications; however, focal spasm was rather unlikely to occur. Furthermore, our results suggest that focal spasm may have a poor prognosis when complicated with DM, even though it tends to be less common, and this finding might be noteworthy.…”
Section: Discussionmentioning
confidence: 46%
“… 9 , 22 This study’s findings also corroborate the fact that VSA patients with focal spasm have a poorer prognosis than those with diffuse spasm. Possible explanations for poorer prognosis with focal spasm include the fact that the degree of ischemia at the time of spasm is greater in focal spasm than in diffuse spasm, 28 as well as the presence or formation of unstable atherosclerotic lesions at the site of focal spasm. 23 , 37 Furthermore, unstable atherosclerotic lesions may exist or form at the site of the focal spasm, possibly with unstable plaques, such as yellowish or thrombosed lesions on coronary angioscopy 24 , 25 , 38 and thrombus formation or intraplaque hemorrhage on optical coherence tomography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracoronary imaging studies revealed that atherosclerotic plaques in focal spastic segments exhibit often vulnerable features, such as high lipid content, macrophage infiltration, intraplaque neovessels and intracoronary thrombi, predisposing to destabilization [ 108 ]. Furthermore Teragawa et al postulated that CAS contributes to thrombogenicity [ 109 ]. This finding might explain the worse prognosis observed in patients with focal compared to diffuse CAS [ 82 ].…”
Section: Invasive Provocative Testingmentioning
confidence: 99%